HIV Infection and risk of postpartum infection, complications and mortality in rural Uganda. Issue 8 (3rd August 2018) - Bebell, Lisa M.; Ngonzi, Joseph; Siedner, Mark J.; Muyindike, Winnie R.; Bwana, Bosco M.; Riley, Laura E.; Boum, Yap; Bangsberg, David R.; Bassett, Ingrid V.
ABSTRACT: HIV infection may increase risk of postpartum infection and infection-related mortality. We hypothesized that postpartum infection incidence and attributable mortality in Mbarara, Uganda would be higher in HIV-infected than HIV-uninfected women. We performed a prospective cohort study of 4231 women presenting to a regional referral hospital in 2015 for delivery or postpartum care. All febrile or hypothermic women, and a subset of randomly selected normothermic women were followed during hospitalization and with 6-week postpartum phone interviews. The primary outcome was in-hospital postpartum infection. Secondary outcomes included in-hospital complications (mortality, re-operation, intensive care unit transfer, need for imaging or blood transfusion) and 6-week mortality. We performed multivariable regression analyses to estimate adjusted differences in each outcome by HIV serostatus. Mean age was 25.2 years and 481 participants (11%) were HIV-infected. Median CD4+ count was 487 (IQR 325, 696) cells/mm 3, and 90% of HIV-infected women (193/215 selected for in-depth survey) were on antiretroviral therapy. Overall, 5% (205/4231) of women developed fever or hypothermia. Cumulative in-hospital postpartum infection incidence was 2.0% and did not differ by HIV status (aOR 1.4, 95% CI 0.6–3.3, P = 0.49). However, more HIV-infected women developed postpartum complications (4.4% vs. 1.2%, P = 0.001). In-hospital mortality was rare (2/1768, 0.1%), and remained so at 6 weeks (4/1526, 0.3%), without differences by HIV serostatus ( P = 1.0 and 0.31, respectively). For women in rural Uganda with high rates of antiretroviral therapy coverage, HIV infection did not predict postpartum infection or mortality, but was associated with increased risk of postpartum complications.